OPTIMASI pH DAN SUHU PRODUKSI METABOLIT ANTIBAKTERI DARI Bacillus tequilensis BSMF SIMBIOSIS Halichondria panicea ASAL PERAIRAN DESA CABBIYA MADURA PADA MEDIA PDA - NINDYA PRAMESTI WARDANI, 051511133037 (2019)
Microorganisms especially sponges-associated bacteria are widely investigated because they can produce antibacterial metabolites, including Bacillus tequilensis BSMF isolated from Halichondria panicea. The production of antibacterial metabolites is influenced by components of growth media, environmental physicochemical factors such as pH, temperature, media, dissolved oxygen conditions, and production time. This research aims to determine pH and optimum temperature of antibacterial metabolites production from Bacillus tequilensis BSMF symbiosis Halichondria panicea in Potato Dextrose Agar (PDA) media. The solid fermentation method was used in the production of Bacillus tequilensis BSMF antibacterial metabolite, while the antibacterial activity test for Bacillus tequilensis BSMF against Staphylococcus aureus ATCC 25923 and Eschericia coli ATCC 25922 used agar diffusion method. The result shows that the optimum pH was reached at pH 8±0,5 and optimum temperature was attained at 32±1oC.